2010
DOI: 10.1029/2009jd013100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of convection on the water isotopic composition of the tropical tropopause layer and tropical stratosphere

Abstract: [1] We present the first in situ measurements of HDO across the tropical tropopause, obtained by the integrated cavity output spectroscopy (ICOS) and Hoxotope water isotope instruments during the Costa Rica Aura Validation Experiment (CR-AVE) and Tropical Composition, Cloud and Climate Coupling (TC4) aircraft campaigns out of Costa Rica in winter and summer, respectively. We use these data to explore the role convection plays in delivering water to the tropical tropopause layer (TTL) and stratosphere. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 41 publications
12
81
1
Order By: Relevance
“…During the wet season, moist air is frequently transported from interior South America by the Bolivian High, a feature associated with the South American monsoon [Lenters and Cook, 1997]. Galewsky et al [2011] showed that dry air from the upper tropical troposphere (UT) reaches the surface at Chajnantor, with mixing ratios as low as 215 ppmv and water vapor D values as low as −540‰, values that are consistent with aircraft measurements from the upper troposphere [Sayres et al, 2010]. They further showed that this dry UT air mixes with moister air from the middle and lower troposphere.…”
Section: The Chajnantor Plateausupporting
confidence: 55%
See 1 more Smart Citation
“…During the wet season, moist air is frequently transported from interior South America by the Bolivian High, a feature associated with the South American monsoon [Lenters and Cook, 1997]. Galewsky et al [2011] showed that dry air from the upper tropical troposphere (UT) reaches the surface at Chajnantor, with mixing ratios as low as 215 ppmv and water vapor D values as low as −540‰, values that are consistent with aircraft measurements from the upper troposphere [Sayres et al, 2010]. They further showed that this dry UT air mixes with moister air from the middle and lower troposphere.…”
Section: The Chajnantor Plateausupporting
confidence: 55%
“…The isotopic composition of water vapor in the stratosphere has been the subject of much debate, because Rayleigh distillation predicts D < −800‰ at the mixing ratios encountered in the lower stratosphere, but measurements indicate −700‰ ≤ D ≤ −550‰ [Sayres et al, 2010;Kuang et al, 2003]. These discrepancies between the Rayleigh model and observations have been interpreted in terms of kinetic fractionation processes in deep convection [Bolot et al, 2013], convective detrainment [Moyer et al, 1996;Kuang et al, 2003;Bony et al, 2008], or mixing [Dessler and Sherwood, 2003].…”
Section: Stable Isotopic Composition Of Water Vapormentioning
confidence: 99%
“…Planned applications for the LTDs beyond Match calculations include the quantification of convective influence to tropical and subtropical upper tropospheric air masses observed by MLS, as previously implemented for highaltitude aircraft in situ observations (Pfister et al, 2001Sayres et al, 2010), and the generation of high resolution "trajectory-mapped" fields such as previously implemented by Schoeberl et al (2007).…”
Section: Appendix A: Mls Lagrangian Trajectory Diagnosticsmentioning
confidence: 99%
“…In the upper troposphere, the water vapor isotopic composition can be measured by satellites (Kuang et al, 2003;Nassar et al, 2007;Steinwagner et al, 2010) or in situ (Webster and Heymsfield, 2003;Sayres et al, 2010) and reflects the role of convection in the transport of water in the upper troposphere and through the tropopause (Moyer et al, 1996). In the mid-troposphere, the water vapor isotopic composition can also be measured by satellite (Worden et al, 2007;Herbin et al, 2009;Schneider and Hase, 2011) and in situ and may give an indication about water cycle processes such as mixing of air masses (Galewsky and Hurley, 2010) or rain reevaporation (Worden et al, 2007).…”
Section: Introductionmentioning
confidence: 99%